2014
DOI: 10.1002/elps.201400159
|View full text |Cite
|
Sign up to set email alerts
|

Determination of six polyynes in Oplopanax horridus and Oplopanax elatus using polyethylene glycol modified reversed migration microemulsion electrokinetic chromatography

Abstract: A PEG-modified reversed migration MEEKC method was developed for simultaneous determination of six polyynes, including oplopandiol, falcarindiol, oplopandiol acetate, (11S, 16S, 9Z)-9,17-octadecadiene-12,14-diyne-1,11,16-triol,1-acetate, oplopantriol B, and oplopantriol A, in Oplopanax horridus and Oplopanax elatus. The running buffer containing 0.8% v/v ethyl acetate, 3.8% w/v SDS, 6.6% v/v n-butanol in 20 mM phosphate buffer (pH 2.5), followed by mixing with propan-2-ol at 30% v/v and PEG-1000 at 15% w/v, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Polyynes have been mostly reported with high contents in both the stem and the root of O. horridus as potential anticancer and antimycobacterial (antituberculosis) natural products. Due to the limited number of analytical chemistry investigations that have been done, only six polyynes have thus far been quantified in the root of O. horridus [ 14 , 15 ]. Phenylpropanoids and lignan glycosides are the other two main natural products from the genus Oplopanax .…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Polyynes have been mostly reported with high contents in both the stem and the root of O. horridus as potential anticancer and antimycobacterial (antituberculosis) natural products. Due to the limited number of analytical chemistry investigations that have been done, only six polyynes have thus far been quantified in the root of O. horridus [ 14 , 15 ]. Phenylpropanoids and lignan glycosides are the other two main natural products from the genus Oplopanax .…”
Section: Phytochemistrymentioning
confidence: 99%
“…For analytical investigation of polyynes in O. horridus , an HPLC fingerprint method was developed to evaluate the stem and berry extracts of O. horridus , which showed that polyynes are not major components in the stem and berries of O. horridus [ 19 ]. For the quantification of polyynes in O. horridus , an online solid-phase extraction HPLC (SPE-HPLC) and a modified reversed migration microemulsion electrokinetic chromatography were validated to quantify polyynes and one polyene in O. horridus [ 14 , 15 ]. The contents of polyynes in the root bark of O. horridus range from 0.029% to 0.15% ( 1 ), 0.025% to 0.13% ( 2 ), 0.077% to 0.31% ( 3 ), 0.24% to 0.43% ( 4 ), 0.26% to 0.67% ( 5 ), and 0.26% to 0.67% ( 6 ), respectively.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Polyynes have been found as the main constituents in the root of O. elatus ( Yang et al, 2014 ). Among them, falcarindiol and oplopandiol were determined to have very high contents in the air-dried root bark.…”
Section: Resultsmentioning
confidence: 99%
“…From 2000, the Chinese State Food and Drug Administration (SFDA) began to require that all injection preparations made from TCM or their raw materials should be standardized by chromatography fingerprint [ 14 ]. In recent years, MEEKC method was used for determination and separation analytes in complex natural products, such as flavonoids and phenolic acids [ 15 ], polyynes [ 16 ], tobacco alkaloids [ 17 ], curcuminoids [ 18 ] and catechins [ 19 ], but few publications have reported on TCM/herbal preparations fingerprint [ 7 ]. Furthermore, conventional chromatography fingerprint methods are mostly qualitative based on a simple comparison of similarity of the fingerprints, and often lack the quantitative assessment of the fingerprints [ 20 ].…”
Section: Introductionmentioning
confidence: 99%